2017
DOI: 10.1371/journal.pone.0178769
|View full text |Cite
|
Sign up to set email alerts
|

Alamandine reduces leptin expression through the c-Src/p38 MAP kinase pathway in adipose tissue

Abstract: ObjectiveObesity is associated with an increased risk of diabetes mellitus, hypertension, and renal dysfunction. Angiotensin 1–7 and alamandine are heptameric renin angiotensin system peptide hormones. Further, alamandine levels increase with renal dysfunction. In the cardiovascular system, angiotensin 1–7 and alamandine produce similar improvements and counterbalance angiotensin II in regulating vascular function. We aimed to determine whether the effect of alamandine on leptin expression and secretion in adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 39 publications
(53 reference statements)
1
26
0
Order By: Relevance
“…It has been reported that alamandine binds to the MrgD receptor to induce NO production by increasing eNOS activity, 1,12 and reduces leptin expression through the PLC/cSrc/p38 MAPK pathway in adipose tissue. 12 Our results showing an attenuation of alamandine-induced ANP secretion by pretreatment with L-NAME, U73122, or SB239063 support published studies showing that the alamandine pathway functions via the MrgD receptor and PLC/p38 MAPK/NO-dependent mechanisms. 1,3,12 Even though we did not show direct evidence that ANP is responsible for the cardioprotection in this study, ANP has been reported to decrease the cardiac load by decreasing the ECF volume and shifting the intravascular fluid into…”
Section: Receptorsupporting
confidence: 88%
“…It has been reported that alamandine binds to the MrgD receptor to induce NO production by increasing eNOS activity, 1,12 and reduces leptin expression through the PLC/cSrc/p38 MAPK pathway in adipose tissue. 12 Our results showing an attenuation of alamandine-induced ANP secretion by pretreatment with L-NAME, U73122, or SB239063 support published studies showing that the alamandine pathway functions via the MrgD receptor and PLC/p38 MAPK/NO-dependent mechanisms. 1,3,12 Even though we did not show direct evidence that ANP is responsible for the cardioprotection in this study, ANP has been reported to decrease the cardiac load by decreasing the ECF volume and shifting the intravascular fluid into…”
Section: Receptorsupporting
confidence: 88%
“…As a result, a chronic low-grade inflammation is present, which excellerates due to SARS-CoV-2 infection induced disbalance of ACE2-ATII. In addition, since ACE2 suppresses leptin levels through alamandine production and activation of the MrgD-receptor/c/Src/p38MAPK pathway we propose that compromising ACE2 function results in a further increase in leptin levels [ 26 ]. This results in a hyperinflammatory local pulmonary response involving local leptin receptors and local ACE2-ATII disbalance.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not find an obesity dependent pattern of subcutaneous adipose ACE-2 mRNA expression at baseline in our human subjects, we identified a significant relationship of ACE-2 expression with estimates of hormonal activity in subcutaneous adipose tissue. As leptin secretion is known to be stimulated by Ang-(1–7) [ 22 ], the observed association of ACE-2 AT with both adipose leptin expression as well as fat mass adjusted circulating leptin level, might be caused by increased Ang-(1–7) level due to higher adipose ACE-2 activity. Given the fact, that increased leptin signaling results in improved insulin sensitivity [ 23 ], this pathway may be also relevant regarding the inter-organ cross talk between adipose tissue and skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%